Preparation method of extruded modified hydroxypropyl starch-based hollow capsule
By introducing hydroxypropyl groups on the starch and using extrusion and puffing treatment, the problems of high gelatinization viscosity, strong regeneration performance and poor mechanical properties of the starch capsules were solved, and modified hydroxypropyl starch-based hollow capsules with optimized performance were prepared to meet the preparation needs of traditional hollow hard capsules.
Patent Information
- Application Number
- CN202510075236.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
Existing starch capsules have problems such as high gelatinization viscosity, strong regeneration performance and poor mechanical properties, which are difficult to meet the needs of traditional hollow hard capsule preparation technology.
By introducing hydroxypropyl groups and applying extrusion puffing treatment, the regeneration performance of starch is weakened, its viscosity is reduced, and the gelling characteristics are improved, and modified hydroxypropyl starch-based hollow capsules are prepared.
The performance optimization of the starch matrix is achieved, meets the needs of the traditional hollow hard capsule preparation process, has good mechanical properties and disintegration performance, and the process is simple, fast, efficient and low-consumption.
Smart Images

Figure CN119818453A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of pharmaceutical excipients, and more specifically to the preparation and application of extruded hydroxypropyl starch. Background Art
[0002] Capsules have become one of the most widely used dosage forms due to their high bioavailability, rapid disintegration in the gastrointestinal tract, good drug stability, and the ability to achieve targeted and timed release of drugs. Although gelatin capsules dominate the market, their shortcomings are gradually emerging: amino acids and compounds containing aldehyde groups in gelatin are prone to cross-linking reactions, which delays the disintegration and dissolution of capsules; as animal-derived products, gelatin capsules are at risk of carrying viruses; the commonly used ethylene oxide sterilization method is potentially corrosive to the human respiratory tract; and the mechanical properties of gelatin capsules are also affected under high temperature and extreme humidity conditions. In addition, gelatin capsules fail to meet the needs of certain specific cultural and religious groups. Therefore, it is particularly important to develop plant capsules with stable and controllable quality.
[0003] As a renewable natural resource, starch has the advantages of abundant sources, low price, and easy biodegradation, and is the most promising substitute for capsule raw materials. However, starch capsules have certain performance deficiencies, such as high gelatinization viscosity, which makes it difficult to increase their dosage in capsule materials; starch is easy to regenerate after film formation, and has poor mechanical properties, which is mainly related to the properties of starch itself. Therefore, in order to further improve the performance of starch-based capsule materials, starch can be modified to improve its application characteristics.
[0004] At present, the development of composite modified starch-based capsule materials mainly involves mixing two or more different modified starches to combine the advantages of different modification methods, thereby making up for the shortcomings of single modified starch. Patent CN108570112A prepares acid-hydrolyzed hydroxypropyl composite modified starch capsules by controlling process parameters such as hydrochloric acid solution concentration, acid hydrolysis time, propylene oxide addition amount and etherification reaction time. While introducing hydroxypropyl with hydrophilic group, it effectively reduces the gelatinization viscosity of starch and improves its gelling properties. Patent CN114948895A prepares oxidized hydroxypropyl pregelatinized composite modified starch by controlling process parameters such as sodium hypochlorite addition amount, propylene oxide addition amount, hydroxypropyl reaction time, etc., which not only improves the mechanical properties of hard capsules, but also effectively reduces the gelatinization viscosity of starch, improves gelling properties and transparency, and enhances its stability. Although oxidation and acid hydrolysis denaturation can reduce the viscosity of starch to a certain extent, these reactions involve multi-step chemical reactions with complex steps, long reaction time, difficult manufacturing process, high manufacturing cost, and difficulty in controlling, which limits their promotion and application. Summary of the invention
[0005] The purpose of the present invention is to provide a hydroxypropyl starch by extrusion expansion in view of the existing problems of starch capsule materials. The composite modified starch weakens the starch regeneration ability while introducing the hydrophilic group hydroxypropyl. By controlling the extrusion expansion conditions such as screw temperature and screw speed, the starch viscosity can be effectively reduced and its gelling properties can be improved, so that the performance of the starch matrix is more in line with the requirements of the traditional hollow hard capsule preparation process. This double modification is simple, fast, efficient, and low-consumption. The modified product has excellent properties. The obtained starch is pre-gelatinized starch, which is easy to dissolve and has the potential for industrial application and reducing production costs.
[0006] A method for preparing extruded and expanded modified hydroxypropyl starch-based hollow capsules comprises the following steps:
[0007] Step 1, preparation of hydroxypropyl starch:
[0008] Mix starch, water and gelatinization inhibitor, set the water bath temperature to 20-25°C, adjust the pH to 10.9-11.20 with sodium hydroxide solution, add propylene oxide as an etherifying agent for reaction, adjust the water bath temperature to 40-50°C and the pH of starch milk to 10.9-11.20 again, react, terminate the reaction with hydrochloric acid solution, centrifuge, wash, dry, crush and sieve the starch milk to obtain hydroxypropyl modified starch;
[0009] Step 2, preparation of extruded hydroxypropyl starch:
[0010] The hydroxypropyl starch prepared in step (1) is adjusted to have a moisture content of 15%-19%, and allowed to stand overnight to balance the moisture; the temperature of the final stage of extrusion and puffing is controlled to be 140-150° C., the screw speed is 110-150 rpm, extruded through a twin-screw extrusion and puffing test machine, and the extrudate is collected and placed in a 40° C. forced air drying oven for 48 hours until dry, and then crushed for later use;
[0011] Step 3, preparation of hollow capsules:
[0012] First, the extruded hydroxypropyl modified starch, plasticizer, gelling agent, coagulant and water are mixed, stirred evenly, heated to 100° C. to completely dissolve the system to obtain a glue solution, dipped in the glue to form a film to obtain a crude capsule, dried at 40° C. for 2 h, and then shelled, cut and fitted to obtain the extruded modified hydroxypropyl starch-based hollow capsule.
[0013] The hydroxypropyl starch samples were subjected to extrusion puffing treatment, which significantly reduced their peak viscosity, disintegration value, final viscosity and regeneration viscosity, reducing the aging tendency of starch; and extrusion will cause a decrease in the disintegration value, making the starch more stable during heating and stirring, effectively reducing the starch viscosity and improving its gelling properties; and extrusion puffing has the advantages of fast speed, high production efficiency, strong versatility, low energy consumption, mixing of multiple ingredients, and help in new product development.
[0014] In one embodiment, the starch raw material in step 1 includes at least one of cassava starch, potato starch or sweet potato starch, and the starch milk mass is 35%-45%.
[0015] In one embodiment, the gelatinization inhibitor in step 1 includes one or more of sodium chloride and sodium sulfate, and the added mass thereof is 10-20% of the dry mass of starch.
[0016] In one embodiment, in step 1, the mass of the etherifying agent added is 5%-10% of the mass of the dry basis of the starch.
[0017] In one embodiment, the moisture content of the starch is adjusted to 17% in step 2.
[0018] In one embodiment, the temperature of the final stage of extrusion expansion in step 2 is 150°C.
[0019] In one embodiment, the screw speed in step 2 is 130 rpm.
[0020] In one embodiment, in step 3, the extruded hydroxypropyl modified starch comprises 16-22 parts by weight, the plasticizer comprises 2.88-3.96 parts by weight, the gelling agent comprises 1.6-2.2 parts by weight, the coagulant aid comprises 0.016-0.022 parts by weight, and the water comprises 78-84 parts by weight.
[0021] In one embodiment, in step 3, the plasticizer includes one or more of glycerol, sorbitol, and stearic acid, the gelling agent includes one or more of κ-carrageenan and I-carrageenan, and the coagulant includes one or more of potassium chloride and sodium citrate.
[0022] In one embodiment, the added mass of the plasticizer in step 3 is 18% of the dry mass of starch.
[0023] In one embodiment, the gelling agent in step 3 is at least one of κ-carrageenan and l-type carrageenan, and the added mass thereof is 5%-15% of the dry mass of starch, and more preferably 10%.
[0024] In one embodiment, the coagulant aid in step 3 is potassium chloride, and the addition amount thereof is 4-20 mmol / L, more preferably 12 mmol / L.
[0025] In one embodiment, the preparation of the hollow capsule in step 3 is specifically as follows:
[0026] Firstly, 16-22 parts by weight of extruded hydroxypropyl modified starch, 2.88-3.96 parts by weight of plasticizer, 2.0 parts by weight of gelling agent, 1.6-2.2 parts by weight of coagulant and 78-84 parts by weight of water are mixed, stirred evenly, and heated to a temperature of 90-100° C. to completely dissolve the system to obtain a glue solution; dipping the glue to form a film: maintaining the temperature at 60-70° C., degassing the glue solution, immersing a template for preparing capsules in the glue solution, dipping the glue to form a film, and obtaining a crude capsule product; finally, drying the crude capsule product at 25-50° C. for 0.5-5h, and then performing shelling, cutting, and sleeve-fitting processes to obtain a hollow starch capsule.
[0027] The second object of the present invention is to provide an extruded hydroxypropyl starch hollow capsule prepared by the above method.
[0028] Beneficial effects:
[0029] (1) Through the etherification reaction, hydroxypropyl groups are introduced, which weakens the hydrogen bonding between starch molecules, promotes the movement of starch molecular chains, changes the structure of starch granules, weakens the regeneration performance of starch, increases the affinity of starch molecules with water, and improves the mechanical properties and disintegration properties of capsules.
[0030] (2) By extruding and puffing hydroxypropyl starch, the starch moisture content, extrusion screw speed and extrusion screw temperature can be precisely adjusted during extrusion to reduce the tendency of starch aging. Extrusion can also reduce the disintegration value, making the starch more stable during heating and stirring. Extrusion can also significantly reduce the viscosity of the starch, thus achieving "high concentration and low viscosity". Extrusion pregelatinization can improve the solubility and rehydration ability of modified starch molecules and their dispersibility in the system, making them dissolve and gel faster, increasing stability and improving the uniformity of the rubber.
[0031] (3) Extruded hydroxypropyl starch hollow capsules do not contain gelatin ingredients, which completely solves the possible safety risks of gelatin. The raw materials are purely plant-based and green and safe. DETAILED DESCRIPTION
[0032] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0033] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0034] Test method:
[0035] Determination of short-range order of extruded hydroxypropyl starch by infrared: The short-range order of starch was determined by Fourier transform infrared spectrometer (FTIR). The sample was accurately weighed and mixed with potassium bromide at a ratio of 1:60 (m:m, dry basis). 60 mg of the mixture was carefully ground and pressed into a sheet. The FT-IR transmission mode was used for scanning. The air background was subtracted and the measurement range was 400-4000 cm -1 , resolution 4cm -1 . Omnic software was used to analyze the wave number 800-1200cm- 1 Fourier self-deconvolution was performed on the area, and the half-peak width and enhancement factor were set to 18 cm -1 and 2.6, calculate 1045cm -1 / 1022cm -1 The peak intensity ratio.
[0036] Determination of gelatinization properties of extruded hydroxypropyl starch: The gelatinization properties of the sample were determined using a rapid viscosity analyzer. 5 g of starch sample was weighed and mixed with deionized water in an RVA aluminum box to prepare a 20% (w / w, dry basis) starch solution, and the gelatinization properties of the sample were determined.
[0037] Adhesive viscosity test: The viscosity of the adhesive was measured using a rheometer. The mold type was parallel plate / parallel plate, the mold diameter was 40 mm, and the gap was 1 mm. The test temperature was set to 50°C, and the linear shear rate change mode was used. The shear rate was changed from 0.1s -1 Increase to 100s -1 .
[0038] Gel temperature test: The gel temperature of the glue was measured by rheometer. A 40mm parallel plate measuring system was selected, with a frequency of 1Hz, a strain of 3%, and a parallel plate spacing of 1mm. The temperature was reduced from 90℃ to 20℃ at a rate of 5℃ / min, balanced for 3min, and then increased to 90℃ at a rate of 5℃ / min. The changes of G′ and G″ during the cooling and heating process were recorded. The curve where the two intersected was the gel temperature of the glue.
[0039] Film tensile strength and elongation at break test: The tensile strength and elongation at break of the film were measured using a texture analyzer. The film was cut into 1×8 cm strips, and the thickness of 8 random points on the strips was measured using a spiral micrometer, and the average value was taken. The mechanical properties of the film were measured using a physical property analyzer equipped with a pulling fixture, with the distance between the upper and lower clamps fixed at 50 mm and the stretching speed at 0.5 mm / s.
[0040] Test of tightness and disintegration time of hollow hard capsules: For tightness test, take 10 capsules, gently pinch the two ends of the capsules with thumb and index finger, rotate and pull them apart, there should be no adhesion, deformation or rupture, then fill them with talcum powder, lock the cap and body, and drop them one by one from a height of 1m onto a wooden board with a thickness of 2cm. There should be no powder leakage; if a small amount of powder leakage occurs, it should not exceed 2 capsules. If it exceeds, take another 10 capsules for retest, and all should meet the requirements.
[0041] Disintegration time test, disintegration time Take 6 capsules of this product, fill them with talcum powder, and check them according to the method under the disintegration time test method (General Rule 0921) for capsules, with a baffle. Each capsule should disintegrate within 10 minutes, and all capsules except broken capsule shells should pass through the sieve. If there are capsule shell fragments that cannot pass through the sieve, but have softened and adhered to the sieve and baffle, it can be considered as meeting the regulations. If 1 capsule does not meet the regulations, another 6 capsules should be taken for retesting, and all should meet the regulations. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The hard capsule prepared by extrusion-modified hydroxypropyl starch in the present invention
[0043] Figure 2 Shear viscosity of EHPS prepared under the same moisture content and different extrusion speed conditions
[0044] Figure 3 Shear viscosity of EHPS prepared under the same rotation speed and different moisture extrusion conditions
[0045] Example 1
[0046] A method for preparing extruded and expanded modified hydroxypropyl starch capsules comprises the following steps:
[0047] (1) Preparation of hydroxypropyl starch:
[0048] Weigh a certain amount of sodium sulfate and starch with a dry starch weight of 15% (w / w), and mix them in distilled water to prepare a starch emulsion with a mass fraction of 40% (w / w, db). Place it in a four-necked flask, set the water bath temperature to 25°C and stir, adjust the pH of the starch emulsion to 11.0 with 1 mol / L sodium hydroxide solution, introduce nitrogen, and add 7% propylene oxide with a dry starch weight at one time. After reacting for 30 minutes, adjust the water bath temperature to 40°C, and adjust the pH of the starch emulsion to 11.0 with 1 mol / L sodium hydroxide solution again. After reacting for 24 hours, adjust the pH of the reaction system to about 6.0 with 1 mol / L hydrochloric acid solution, wash with water, dry at 40°C, and grind through a 100-mesh sieve to obtain the product.
[0049] (2) Preparation of extruded hydroxypropyl starch:
[0050] Adjust the moisture content of the hydroxypropyl starch prepared in step (1) to 17% and place it in a ziplock bag overnight to balance the moisture. Extrude the hydroxypropyl starch raw material after moisture balance under the following extrusion conditions, where the extrusion temperature is: 50°C for zone 1, 60°C for zone 2, 110°C for zone 3, and 150°C for zone 4; the screw speed is 110rpm, and the feed speed is 4.4rpm. Collect the extrudates and place them in a 40°C forced air drying oven for 24 hours until dry, then crush them through an 80-mesh sieve for later use.
[0051] (3) Preparation of extruded modified hydroxypropyl starch empty capsules:
[0052] First, 20 parts by weight of extruded hydroxypropyl modified starch, 3.6 parts by weight of glycerol, 2.0 parts by weight of κ-carrageenan, 0.0745 parts by weight of potassium chloride, and 80 parts by weight of water are mixed, stirred evenly, and heated to a temperature of 100°C to completely dissolve the system to obtain a glue solution, wherein the extruded hydroxypropyl starch is prepared by the method described in the first aspect of step (2); dip in glue and make a film: maintain the temperature at 70°C, degas the glue solution, immerse the template for preparing capsules in the glue solution, dip in glue and make a film to obtain a crude capsule; finally, dry the crude capsule at 40°C for 2 hours, then shell, cut, and fit together to obtain an extruded hydroxypropyl starch capsule. The hard capsule prepared by using extruded modified hydroxypropyl starch in the present invention is as follows: Figure 1 .
[0053] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0054] Example 2
[0055] The extrusion conditions in step (2) of Example 1 were adjusted, wherein the extrusion temperatures were: 50°C for zone 1, 60°C for zone 2, 110°C for zone 3, and 150°C for zone 4; the screw speed was 120 rpm, and the feed speed was 4.8 rpm. The other conditions were kept the same as those in Example 1, and extruded hydroxypropyl starch capsules were obtained.
[0056] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0057] Example 3
[0058] The extrusion conditions in step (2) of Example 1 were adjusted, wherein the extrusion temperatures were: 50°C for zone 1, 60°C for zone 2, 110°C for zone 3, and 150°C for zone 4; the screw speed was 130 rpm, and the feed speed was 5.2 rpm.
[0059] The other conditions were kept the same as those in Example 1 to obtain extruded hydroxypropyl starch capsules.
[0060] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0061] Example 4
[0062] The extrusion conditions in step (2) of Example 1 were adjusted, wherein the extrusion temperatures were: 50°C for zone 1, 60°C for zone 2, 110°C for zone 3, and 150°C for zone 4; the screw speed was 140 rpm, and the feed speed was 5.6 rpm. The other conditions were kept the same as those in Example 1, and extruded hydroxypropyl starch capsules were obtained.
[0063] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0064] Example 5
[0065] The extrusion conditions in step (2) of Example 1 were adjusted, wherein the extrusion temperatures were: 50°C for zone 1, 60°C for zone 2, 110°C for zone 3, and 150°C for zone 4; the screw speed was 150 rpm, and the feed speed was 6.0 rpm. The other conditions were kept the same as those in Example 1, and extruded hydroxypropyl starch capsules were obtained.
[0066] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0067] Embodiment 6:
[0068] The moisture content of the hydroxypropyl starch in step (2) of Example 3 was adjusted to 15%. Other conditions were kept the same as those of Example 3 to obtain extruded hydroxypropyl starch capsules.
[0069] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0070] Embodiment 7:
[0071] The moisture content of the hydroxypropyl starch in step (2) of Example 3 was adjusted to 19%. Other conditions were kept the same as those of Example 3 to obtain extruded hydroxypropyl starch capsules.
[0072] In order to investigate the practical application performance of extruded modified hydroxypropyl starch, the short-range order and gelatinization characteristics of the extruded modified hydroxypropyl starch in step (3) were measured in this embodiment. The viscosity of the glue prepared by extruded modified hydroxypropyl starch, the gel temperature of the starch paste prepared by extruded modified hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruded modified hydroxypropyl starch, and the brittleness and disintegration performance of the extruded modified hydroxypropyl starch capsule prepared in step (3) were measured. The test results are shown in Tables 1, 2 and 3.
[0073] As can be seen from the table, compared with cassava starch, the R 1045 / 1022 The infrared short-range orderliness is significantly improved, indicating that the extrusion expansion hydroxypropyl treatment can significantly improve the short-range orderliness of starch, and can form an ordered gel network structure when preparing gel, enhancing the gel strength. At the same time, because of the formation of a uniform and stable structure, the water holding capacity of the formed capsule material will also be enhanced, and the starch is not easy to regenerate. With the increase of the screw speed, R 1045 / 1022 It shows a trend of increasing first and then decreasing. When the moisture content is constant, the short-range order of Example 3 is the highest, indicating that appropriate improvement is conducive to improving the short-range order of starch, while when the screw speed is too high, it will damage the order of starch particles. The gelatinization characteristics show that the disintegration value and the regeneration value of cassava hydroxypropyl starch decrease after extrusion puffing treatment, and the starch is not easy to regenerate.
[0074] After extrusion and expansion of hydroxypropyl starch and colloid compounding, the gel temperature is moderate, and the tensile strength of the prepared starch-based film is high. The disintegration performance of starch-based capsules is good. It can be seen from Table 1 that under the condition of constant moisture content, the tensile strength of starch film increases with the increase of screw speed; under the condition of constant screw speed, the higher the moisture content of starch, the greater the tensile strength, but the elongation at break does not change significantly. The increase in screw speed usually leads to an increase in the shear force of starch in the extruder. This increased shear force helps the interaction between starch molecules, promotes the arrangement and partial recrystallization of molecular chains, and thus improves the tensile strength of starch film. In addition, a higher screw speed can increase the degree of plasticization of starch, making it easier for starch molecules to flow and rearrange during extrusion, which helps to improve the uniformity and tensile strength of the film. However, the increase in screw speed may also lead to a shortened residence time of starch in the extruder. If the shear force is too strong or the residence time is too short, the structure of starch molecules may be destroyed, and the tensile strength may be reduced. Therefore, a suitable screw speed can balance the shear force and residence time to obtain a better tensile strength. At a certain screw speed, increasing the moisture content helps the gelatinization process of starch, because moisture as a plasticizer can reduce the interaction between starch molecules, making it easier for starch to flow and rearrange. Appropriate moisture content can improve the plasticity and flexibility of starch films, thereby increasing tensile strength. The tightness and disintegration time of starch capsules produced under appropriate extrusion conditions are both qualified.
[0075] Table 1
[0076]
[0077] Table 2 Infrared short-range order of extruded hydroxypropyl starch of Examples 1-7
[0078]
[0079]
[0080] Table 3 Gelatinization properties of extruded hydroxypropyl starch in Examples 1-7
[0081]
[0082] Comparative Example 1
[0083] The step (1) of subjecting cassava starch to hydroxypropylation and the step (2) of subjecting hydroxypropyl starch to extrusion puffing in Example 1 were omitted, and the rest of the steps were the same as in Example 1.
[0084] In order to investigate the practical application performance of common cassava starch, this comparative example measured the viscosity of the glue prepared from common cassava starch and the mechanical properties (tensile strength, elongation at break) of the starch film prepared from common cassava starch. The test results are shown in Table 4.
[0085] The sample that has not been subjected to hydroxypropyl modification and extrusion expansion treatment has a high viscosity of the glue and poor film-forming property. The starch film made from ordinary cassava starch has poor gel properties, a slower drying speed than the embodiment, uneven shrinkage, uneven color and texture, and many bubbles; the film has low tensile strength and elongation at break, which cannot meet the tensile strength and elongation at break requirements of hard capsules, and is therefore not suitable for preparing hard capsules, and cannot meet the requirements of the hard capsule preparation process at all.
[0086] Table 4
[0087]
[0088] Comparative Example 2
[0089] The step (3) of extruding and puffing the hydroxypropyl starch in Example 1 was omitted, and the rest of the steps were the same as in Example 1.
[0090] In order to investigate the practical application performance of hydroxypropyl starch, this comparative example measured the viscosity of the glue prepared from hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared from hydroxypropyl starch, and the friability and disintegration properties of the prepared starch-based hard capsules. And the friability and disintegration properties of the extrusion-modified hydroxypropyl starch capsules prepared in step (3). The test results are shown in Table 5.
[0091] The results show that: Comparative Example 2 does not use extrusion puffing treatment, and the relevant properties of the obtained hydroxypropyl starch are greatly improved compared with the unmodified ordinary cassava starch in Comparative Example 1; however, the viscosity of the glue prepared by hydroxypropyl starch is still too large, and it does not have the characteristics of "high concentration and low viscosity", the glue has poor formability, the sol is difficult, the film-forming property is poor, and the color and thickness of the formed starch film are uneven and there are bubbles. The mechanical properties (tensile strength and elongation at break) of the film are far worse than those of the embodiment, and cannot meet the production requirements of hard capsules.
[0092] Table 5
[0093]
[0094] Comparative Examples 3-11
[0095] The preparation method of Example 1 is referred to, except that the material moisture, screw speed and extrusion expansion temperature are regulated to prepare extrusion modified hydroxypropyl starch. The viscosity of the glue prepared by the extrusion modified hydroxypropyl starch of this comparative example in step (3), the mechanical properties (tensile strength, elongation at break) of the starch film prepared by the extrusion modified hydroxypropyl starch of this comparative example, and the brittleness and disintegration properties of the extrusion modified hydroxypropyl starch-based hollow capsule prepared in step (3) of this comparative example are measured. The test results are shown in Table 6.
[0096] The present invention has found that when preparing the hard capsule, the viscosity of the glue should be controlled within the range of 900-1300 mPa·s. The comparison results of Comparative Examples 3-11 and Example 1 show that only when the material moisture is controlled at 17%-19%, the extrusion expansion temperature is 140℃-150℃, the screw speed is 110rpm-150rpm, and the amount of propylene oxide added is 6.5-8%, the extrusion modified hydroxypropyl starch prepared by the method of the present invention can simultaneously achieve the following properties, which meets the requirements of the hard capsule preparation process: the viscosity of the prepared glue is controlled within the range of 900-1200 mPa·s; the film tensile strength is above 25MPa, the film elongation at break is above 10%, the prepared hard capsule is neat and smooth, the brittleness is 0, and the disintegration time is within 10min. However, when the moisture content of the material is too high, the puffing temperature is too low, or the screw speed is too low, the viscosity of the gelatin cannot be controlled within the range of 900-1300 mPa·s, which is not conducive to the smooth progress of the hard capsule preparation process and it is difficult to successfully prepare hard capsule products that are neat, smooth, leak-free, and meet the requirements for friability and disintegration time.
[0097] Table 6 Effects of material moisture, screw speed and extrusion temperature on the properties of extruded modified hydroxypropyl starch
[0098]
[0099] Note: “-” means no result was detected.
[0100] It can be seen that the extruded modified hydroxypropyl starch prepared by the present invention after optimizing parameters based on a specific process can effectively control the viscosity of the starch colloid, improve its gelling properties, and give the starch film relatively excellent mechanical properties, making it more in line with the requirements of the hard capsule preparation process.
[0101] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing extruded and expanded modified hydroxypropyl starch-based hollow capsules, characterized in that: The following steps are involved: Step 1, preparation of hydroxypropyl starch: Mix starch, water and gelatinization inhibitor, set the water bath temperature to 20-25°C, adjust the pH to 10.9-11.20 with sodium hydroxide solution, add propylene oxide as an etherifying agent for reaction, adjust the water bath temperature to 40-50°C and the pH of starch milk to 10.9-11.20 again, react, terminate the reaction with hydrochloric acid solution, centrifuge, wash, dry, crush and sieve the starch milk to obtain hydroxypropyl modified starch; Step 2, preparation of extruded hydroxypropyl starch: The hydroxypropyl starch prepared in step (1) is adjusted to have a moisture content of 15%-19%, and allowed to stand overnight to balance the moisture; the temperature of the final stage of extrusion and puffing is controlled to be 140-150° C., the screw speed is 110-150 rpm, extruded through a twin-screw extrusion and puffing test machine, and the extrudate is collected and placed in a 40° C. forced air drying oven for 48 hours until dry, and then crushed for later use; Step 3, preparation of hollow capsules: First, the extruded hydroxypropyl modified starch, plasticizer, gelling agent, coagulant and water are mixed, stirred evenly, heated to 100° C. to completely dissolve the system to obtain a glue solution, dipped in the glue to form a film to obtain a crude capsule, dried at 40° C. for 2 h, and then shelled, cut and fitted to obtain the extruded modified hydroxypropyl starch-based hollow capsule.
2. The method for preparing the extruded and expanded modified hydroxypropyl starch-based hollow capsules according to claim 1, characterized in that: The starch raw material in step (1) includes at least one of cassava starch, potato starch or sweet potato starch, and the starch milk mass is 35%-45%.
3. The method for preparing the extruded and expanded modified hydroxypropyl starch-based hollow capsules according to claim 1, characterized in that: In step (1), the gelatinization inhibitor includes one or more of sodium chloride and sodium sulfate, and the added mass thereof is 10-20% of the dry mass of starch.
4. The method for preparing the extruded and expanded modified hydroxypropyl starch-based hollow capsules according to claim 1, characterized in that: In step (1), the added mass of the etherifying agent is 5%-10% of the dry mass of the starch.
5. The method for preparing the extruded hydroxypropyl starch hollow hard capsule according to claim 1, characterized in that: In step 3, the extruded hydroxypropyl modified starch comprises 16-22 parts by weight, the plasticizer comprises 2.88-3.96 parts by weight, the gelling agent comprises 1.6-2.2 parts by weight, the coagulant aid comprises 0.016-0.022 parts by weight, and the water comprises 78-84 parts by weight.
6. The method for preparing the extruded hydroxypropyl starch hollow hard capsule according to claim 1 or 5, characterized in that: In step 3, the plasticizer includes one or more of glycerol, sorbitol, and stearic acid, the gelling agent includes one or more of κ-carrageenan and I-carrageenan, and the coagulant includes one or more of potassium chloride and sodium citrate.
7. Extruded hydroxypropyl starch hollow capsules prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Composite modified starch-based empty hard capsule
CN108570112A
Composite modified starch-based soft capsule
CN114948895A